The different faces of athletes in Iceland : experiences and views of prejudice and discrimination among athletes with various ethnic backgrounds - Sigurður Jefferson Guarino 2001- (2023)
This thesis explores the evolving landscape of Icelandic sports, where increasing ethnic diversity intersects with the challenges of racism and ethnic prejudice. Sports are recognized as a unifying activity that transcends societal divisions. This study examines the prevalence and underlying issues of discrimination and bias that infiltrate the Icelandic sports world. A quantitative survey of 27 athletes across various sports disciplines, the research examines perceptions and personal experiences of racism and prejudice, alongside their impacts on mental health and athletic performance. Findings indicate that a significant proportion of athletes (51.9%) view racism as a concern in Icelandic sports, with a higher percentage (63%) acknowledging the prevalence of ethnic prejudice. Notably, 66.7% of participants reported personal encounters with discrimination, primarily from spectators and teammates. While these experiences are acknowledged, a handful of athletes reported an adverse impact on mental health (22.2%) and performance (14.8%). These results highlight a critical gap between the recognition of racial issues and their acknowledged impact on athletes' well-being and performance. The thesis underscores the need for a deeper understanding of racial dynamics in sports with further academic research and calls for proactive strategies to develop an inclusive and respectful athletic environment in Iceland. Keywords: Prejudice, discrimination, biases, mental health, diversity, sports Þessi ritgerð fjallar um samfélagstengda þróun innan íþrótta á Íslandi, þar sem aukinn fjölbreytni í samfélaginu kallar á ýmsar áskoranir fyrir þá sem koma af erlendum uppruna eða eiga blandaðan bakgrunn. Fjallað er um þær áskoranir sem felast í kynþáttafordómum og/eða þjóðernisfordómum. Íþróttir eru almennt taldar vera sameinandi afl, sem jafnvel getur aðstoðað við að yfirstíga ýmsar samfélagslegar áskoranir. Þessi rannsókn skoðar algengi mismununar og hlutdrægni sem getur átt sér stað í íþróttum á Íslandi. Rannsóknin byggir á ...